Integrative taxonomy and phylogenetic systematics of the Triatoma rubrovaria subcomplex (Hemiptera, Triatominae) - da Silva, Lucas Abrantes [UNESP]; Belintani, Tiago; de Paiva, Vinícius Fernandes; Nascimento, Juliana Damieli; Rimoldi, Aline; Gardim, Sueli [UNESP]; Rocha, Cláudia Solano [UNESP]; de Mello, Fernanda; Obara, Marcos Takashi; de Oliveira, Jader [UNESP]; da Rosa, João Aristeu [UNESP] (Elsevier, 2023)
Triatoma rubrovaria subcomplex consists of T. carcavalloi, T. circummaculata, T. klugi, T. limai, T. oliveirai, T. pintodiasi, T. rubrovaria, T. patagonica and T. guasayana, which can be vectors of Trypanosoma cruzi, the etiologic agent of Chagas disease. In this study, morphological, morphometric, and genetic characters of T. circummaculata, T. pintodiasi, T. carcavalloi, T. klugi, and T. rubrovaria were analyzed in view of the integrative taxonomy and phylogeny of the T. rubrovaria subcomplex. Molecular studies were carried out through the sequencing and analysis of the mitochondrial genes COI and CytB, nuclear genes ITS I, ITS 2, 16S, and 28S from rDNA and rescued a monophyletic group. Furthermore, differential morphological characters were found among the five species in the pronotum, scutellum, stridulatory sulcus, male genitalia, and external female genitalia. Finally, morphometric analyses made it possible to differentiate the five species. Phylogenetic analyzes rescued the relationship of T. pintodiasi with members of the T. rubrovaria subcomplex and demonstrated that this subcomplex is a monophyletic group composed of the species T. carcavalloi, T. circummaculata, T. klugi, T. guasayana, T. limai, T. oliveirai, T. patagonica, T. pintodiasi, and T. rubrovaria. Furthermore, through integrative taxonomy, it was possible to confirm the specific status of the species T. carcavalloi, T. circummaculata, T. pintodiasi, T. klugi, and T. rubrovaria, offering new useful morphological characters for the differentiation and characterization of these potential vectors and distributed in Southern Brazil.
Keywords: Mitochondrial gene; Morphology; Morphometry; Nuclear gene; Phylogeny; Reduviidae